Developmental Trends of Graduate Education in China - Xu, Yanru; Liu, Ji’an (International Higher Education, 2022)
This article offers a snapshot of developmental trends in Chinese graduate education for the past twenty years by examining the differentiated expansion of levels, types, disciplines, and gender composition. Also, the drivers for expansion are analyzed in terms of domestic demands for graduate education and for upgrading research and development workforces. Finally, the potential outcomes for future development are explored.